Intercultural communication for managers - Goodman, Michael B. (2013 digital library., 2013)
People have always found a way to trade with one another, overcoming enormous barriers. Nations that fought for centuries came together after World War II dedicated to a plan that would let them thrive in peace. Business and trade relationships were the foundation. This book is based on the simple concept that people who partner in business tend to work together in peace more often than not. Education is also a fundamental building block for successful global relationships.